Cross-cultural validation and reference norms for the DCDDaily-Q questionnaire Chinese version (DCDDaily-Q-CN): evaluating children’s motor performance in activities of daily living - Meihuan Huang; Yujun Zhan; Haishan Zhou; Ping Song; Yanping Fan; Yang Lu; Yijing Chen; Zhen Lv; Qing Liu; Guojun Yun; Jianguo Cao (Frontiers in Public Health)
BackgroundThe DCDDaily-questionnaire (DCDDaliy-Q) evaluates children’s performance and participation in motor-based activities of daily living (ADLs), meeting diagnostic criterion B for developmental coordination disorder (DCD). Currently, there are no Chinese translations or growth references available. Thus, this study aimed to culturally adapt, validate, and establish reference norms for the DCDDaily-Q in Chinese children.MethodsThe original scale was translated and culturally adapted into Chinese (DCDDaily-Q-CN) following international guidelines. Normative data of typically developing children (n = 1936, aged 5–10) were gathered from 14 randomly chosen mainstream schools in a large migrant city. Thirty children (aged 5–10 years) diagnosed with DCD were recruited through clinical referrals, and a matched control group (n = 30) was randomly selected from the reference group. Reference norms with growth curves and psychometric properties were analyzed.ResultsSex-specific growth curves with percentiles and cut-off values of the DCDDaily-Q-CN in children aged 5–10 years were established. The instrument demonstrated excellent internal consistency across the total and the three subscales (Cronbach’s alpha = 0.83–0.91). The confirmatory factor analysis showed a good fit for the original three-factor model (CFI = 0.936, RMSEA = 0.049). Moderate to strong correlations were found between the DCDDaily-Q-CN performance total score and the DCDQ-R (rs = −0.54) and MABC-2 total scores (rs = −0.68). The total performance score effectively differentiated between children with DCD and controls (U = 9.0, p < 0.001), with a cutoff score of 45, demonstrating a sensitivity of 93% (95%CI: 77–99%) and specificity of 90% (95%CI: 74–98%).ConclusionThe findings support that the DCDDaily-Q-CN is a reliable and valid measure to assess participation and performance in motor-based ADLs and fulfill criterion B of the diagnostic criteria for DCD.